The Importance of Developing a Territorial Planning Scheme for the Republic of Uzbekistan (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The territorial planning scheme of the Republic of Uzbekistan, ensuring the socio-economic development of the country, maintaining environmental stability, taking into account demographic changes, and developing industry and agriculture were considered and development plans were drawn up.